A Model Of Cultivating Morality In Fikih Learning Strategies Course - Arlina Arlina; Abdul Halim Nasution; Nur A'yuni (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to find a model of instilling morals carried out by lecturers in the fiqh learning strategy course. This research uses a qualitative approach with a descriptive study method, meaning that the researcher describes the actual phenomena related to the model of inculcating morals in the lecture process. Collecting research data using the method of observation, interviews and documentation studies. Data analysis using data reduction techniques, data presentation, and drawing conclusions. The data sources for this research were lecturers of the science learning strategy course (key informants) and students (supporting informants) at FITK UIN North Sumatra Medan. Test the validity of the research using data triangulation techniques. The results of this study concluded that the model of inculcating morals was carried out effectively and on target by lecturers in the fiqh learning strategy course towards students. This is characterized by two aspects, namely (1) instilling morals in students is given in learning activities, including preliminary activities, core activities, and closing activities; and (2) moral values that are instilled in students include morals towards Allah SWT, morals towards Rasulullah SAW, morals to oneself, and morals to fellow human beings.